"We Who Champion the Unborn": Racial Poisons, Eugenics, and the Campaign for Prohibition. Issue 1 (2022) - Lombardo, Paul A.
Abstract: Dr. Caleb Williams Saleeby was the author of Parenthood and Race Culture, one of the first monographs on eugenics and the book that popularized the term "racial poison." The goal of eradicating the racial poisons and the harm they caused — particularly infant morbidity and mortality — provided common ground for early 20th century reformers, and their concerns fed the growing support for legal prohibition of alcohol.